GAMBARAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) SISWA SISWI SEKOLAH DASAR NEGERI III KEMIRI KECAMATAN KEMIRI KABUPATEN TANGERANG - Muhamad Rizki Fadhlillah (Nusantara Hasana Journal, 2023)
Empirical data that PHBS is a very important indicator for public health in an area and the implementation of PHBS for students at SDN 3 Kemiri has never been studied specifically. This study was to determine the description of PHBS in SDN 3 Kemiri. Method used in this research is descriptive quantitative method with survey technique. The affordable population in this study were all 187 students of SDN 3 Kemiri class IV, V and VI. Samples were taken proportionally as much as 32%, namely 60 people. The method used in this study is a quantitative method with descriptive analysis. The research showed that the implementation of PHBS at SDN 3 Kemiri was in the medium category 6%, the high category 35.33% and the very high category 58.33%. The PHBS of the 3 Kemiri State Elementary School students showed that most of them had implemented indicators of clean and healthy living behavior. Indicators that need attention to improve PHBS for elementary school students at Kemiri 3 Elementary School are CTPS before carrying out activities, community service habits to clean mosquito larvae, habit of avoiding cigarette smoke when someone smokes and regular exercise habits according to physical abilities.